Long-term follow-up of a phase II trial of oral altretamine for consolidation of clinical complete remission in women with stage III epithelial ovarian cancer in the Southwest Oncology Group. Issue 2 (1st February 2004) - Alberts, D. S.; Jiang, C.; Liu, P. Y.; Wilczynski, S.; Markman, M.; Rothenberg, M. L.
Abstract : Objective: This report provides follow-up progression-free survival (PFS) and median survival data for women who achieved clinical complete remission (cCR) from stage III ovarian cancer after first-line therapy and were treated with altretamine consolidation therapy. Methods: Patients who enrolled in the SWOG 9326 study from September 1993 to July 1997 were required to have documented cCR from stage III ovarian cancer following front-line platinum-based therapy. Treatment consisted of 6 months of oral altretamine at 260 mg/m 2 /day for 14 consecutive days of a 28-day cycle. Results: Ninety-seven of 112 enrolled patients were evaluable for efficacy. This report presents median 6.2-year follow-up, dating from study registration. Median PFS was 28 (95% CI: 19–43) months. Median PFS for patients with optimal disease was 45 (95% CI: 27–48) months and for patients with suboptimal disease was 17 (95% CI: 12–26) months. Twenty-six of 61 (43%) patients with optimally debulked lesions and 5 of 36 (14%) patients with suboptimally debulked lesions remained disease free. Median survival of patients with optimally debulked disease has not been reached; median survival of patients with suboptimally debulked disease was 39 (95% CI: 19–51) months. No treatment-related adverse events were reported during the follow-up period. Conclusions: Consolidation therapy with oral altretamine was generally well tolerated and associated with prolonged progression-free and overall survival in the Phase II setting.